Can noncomplementarity of agency lead to successful problem solving? A case study on students' interpersonal behaviors in mathematical problem-solving collaboration. (December 2022) - Haataja, Eeva S.H.; Chan, Man Ching Esther; Salonen, Visajaani; Clarke, David J.
Abstract: In student collaboration, purposeful peer interaction crucial for success on the task. Such collaboration requires adequate and purposeful student agency. Theoretically, the between-individual complementarity of agency behaviors enhances purposeful interaction. However, the level of agency of group members can disrupt the collaborative interactions. We conducted a case study of collaborative mathematical problem solving, where one student's behaviors of noncomplementary agency characterized the group interaction. We examined the video recording of the group by continuous quantitative coding of students' agency behaviors and segmented the interaction process into four phases. We analyzed qualitatively these phases based on the verbal transcript. We found that the target student's agency grew in relation to the other students despite her lack of mathematical competence. The findings provide us with a new perspective to understand the role of the situational individual agency in collaborative learning that underlines the tolerance of noncomplementarity of agency in student collaboration. Highlights: A case of student group work was found to contradict interpersonal theory. Continuous coding can capture momentary agency behaviors in the group level. Noncomplementary interpersonal behaviors can lead to successful collaboration. Theoretically, situational and structural agency are in relation to each other.